Uterine leiomyoma is associated with the risk of developing endometriosis: A nationwide cohort study involving 156,195 women. - Kent Yu-Hsien Lin (Public Library of Science (PLoS), 2021)
Objective Evidence for an association between uterine leiomyoma and increased risk of endometriosis is limited by small sample sizes and short follow-up periods. We assessed this association in a large nationwide sample with 14 years of data. Design Data were sourced from Taiwan's Longitudinal Health Insurance Database 2000 (LHID2000). Materials and methods We identified 31,239 women aged ≥20 years diagnosed with uterine leiomyoma (International Classification of Disease, Ninth Revision, Clinical Modification [ICD-9-CM] code 218) between Jan 1, 2000 and Dec 31, 2012, who were matched with 124,956 controls (1:4) by 5-year age groups and year of diagnosis. Follow-up was from the date of LHID2000 entry to the first occurrence of endometriosis, loss to follow-up, insurance termination, or until December 31, 2013, whichever was earlier. Results In Cox regression analysis, the adjusted hazard ratio (aHR) for endometriosis in women with uterine leiomyoma was 6.44 (95% CI, 6.18, 6.72) compared with controls. The risk of endometriosis was significantly increased in women with uterine leiomyoma and comorbidities of tube-ovarian infection (aHR 2.86; 95% CI, 1.28, 6.36), endometritis (1.14; 1.06, 1.24), infertility (1.26; 1.16, 1.37), or allergic diseases (1.11; 1.05, 1.17). Having both uterine leiomyoma and endometritis significantly increased the risk of endometriosis (aHR 6.73; 95% CI, 6.07, 7.45) versus having only uterine leiomyoma (6.61; 6.33, 6.91) or endometritis (1.49; 1.31, 1.69). Similarly, having both uterine leiomyoma and infertility significantly increased the risk of endometriosis (aHR 6.95; 95% CI, 6.21, 7.78) versus having only uterine leiomyoma (6.66; 6.38, 6.96) or infertility (1.78; 1.57, 2.02). Conclusions A diagnosis of uterine leiomyoma appears to increase the risk of endometriosis. Patients presenting with uterine fibroids should be encouraged to give informed consent for possible simultaneous surgical treatment of endometriosis.